Internet connectivity disruption in Paraguay (Paraguay) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Paraguay. Data sourced from IODA.
Network Disruption Incident ID: PY-2026-0022. Severity: critical. Confidence: 67%